The CAD concept for stellarator-type magnetic systems - Vorobyova, V.P.; Martynov, S.A.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2002)
The paper describes the computer-aided design (CAD) concept for stellarator-type magnetic systems. Consideration is given to the main peculiarities, principles, and dialog organization and design stages of the CAD. The practical realization of the concept is illustrated by specific examples.